Evaluation and treatment of postconcussive symptoms - Thomas W. McAllister; David B. Arciniegas (2002)
Postconcussive symptoms such as headache, dizziness, irritability, and difficulties with memory and attention are reported frequently after traumatic brain injuries (TBI) of all severities. The etiology of these symptoms in individuals with mild TBI has been a subject of some controversy with theories ranging from neural damage to malingering. Furthermore, although the term postconcussive syndrome is commonly used clinically and in the scientific literature, it is not clear that postconcussive symptoms constitute a syndrome per se. Instead, it may be the case that the various symptoms that commonly co-occur after TBI are relatively independent consequences of a single neurological event. In other words, because the locations and severity of injury vary between individuals despite ostensibly similar injuries, it follows that there should be variations in symptom type and severity between individuals as well. This article reviews the sequelae and natural course of recovery from mild TBI, the evidence regarding both persistent postconcussive symptoms and the postconcussive syndrome, and outlines an approach to the assessment and treatment of individuals with these symptoms after TBI.